Sobre los números de Hal y Lah - Piza Volio, Eduardo (2002)
In this article we study some properties concerning the Hal (Hkn ) and Lah numbers (Lkn), which are those that arise in the theory of combinatorics in association with the ‘upward and downward factorial polynomials’ [x]n and [x]n. We establish the corresponding recurrence formulas, the generating functions and the closed formulas for this family of numbers, among others properties.